Nitrification and Nitrifying Bacteria in a Coastal Microbial Mat - Fan, Haoxin; Bolhuis, Henk; Stal, Lucas J. (Frontiers in Microbiology, 2015)
The first step of nitrification, the oxidation of ammonia to nitrite, can be performed by ammonia-oxidizing archaea (AOA) or ammonium-oxidizing bacteria (AOB). We investigated the presence of these two groups in three structurally different types of coastal microbial mats that develop along the tidal gradient on the North Sea beach of the Dutch barrier island Schiermonnikoog. The abundance and transcription of amoA, a gene encoding for the alpha subunit of ammonia monooxygenase that is present in both AOA and AOB, were assessed and the potential nitrification rates in these mats were measured. The potential nitrification rates in the three mat types were highest in autumn and lowest in summer. AOB and AOA amoA genes were present in all three mat types. The composition of the AOA and AOB communities in the mats of the tidal and intertidal stations, based on the diversity of amoA, were similar and clustered separately from the supratidal microbial mat. In all three mats AOB amoA genes were significantly more abundant than AOA amoA genes. The abundance of neither AOB nor AOA amoA genes correlated with the potential nitrification rates, but AOB amoA transcripts were positively correlated with the potential nitrification rate. The composition and abundance of amoA genes seemed to be partly driven by salinity, ammonium, temperature and the nitrate/nitrite concentration. We conclude that AOB are responsible for the bulk of the ammonium oxidation in these coastal microbial mats.